Experimental marketing at pondok pesantren Indonesia - Sri Intan Wahyuni; Melisa Kurnia Fitri; Syarifatul Hayati (Edusoshum : Journal of Islamic Education and Social Humanities, 2024)
One of the objectives of this reaserch is to find out how Experiential Marketing is impelented at Pondok Pesantren. Judging from the growth and development experienced by Pondok Pesantren Syafa’aturrasul from 2018 to 2022, public interest continues to increase, so that the number of students at Pondok Pesantren Syafa’aturrasul currently stands at 1500 students. Seeing this potential, the researcher was interested in conducting research on experiential marketing conducted by Pondok Pesantren This research is a qualitative descriptive study using triangulation to test the validity of the data. The data collection techniques are interviews, observation, documentation and questionnaires. Based on data analysis, strategies for implementing experiential marketing, namely in terms of sense, feel, think, act and relate marketing. The result of data analysis show that Pondok Pesantren  implements experiential marketing well.